Unternehmen: Partner der Jugend. Bundesinitiative. (Informationsmappe). - (:unkn) unknown (My University, 1998)
UPJ im Internet: www.upj-online.de.
Keywords: Sozialinfrastruktur; Sozialarbeit; Jugendhilfe; Partizipation; Kooperation; Jugendlicher; Wirtschaft; Wirtschaftsunternehmen; Sponsoring; Spende; Jugendarbeit; Jugendsozialarbeit; Projektbeschreibung; Soziale Stadt